Complete resolution of stage II avascular necrosis affecting three joints by hyperbaric oxygen in a patient with sickle cell disease: A case report - Alshurafa, Awni; Elhissi, Mohammad; Yassin, Mohamed A. (Frontiers in Medicine, 2022)
Avascular necrosis (AVN) or joint osteonecrosis is a debilitating complication of sickle cell disease, increasing the disease burden on both patients and healthcare systems. AVN can be radiologically categorized into early and late stages depending on the extent of the disease. Management of AVN is challenging and controversial. Generally, it includes conservative measures for early disease to preserve the joint for as long as possible and surgical management for more advanced diseases. Hyperbaric oxygen (HBO) therapy can be used as primary or adjunctive therapy for different medical disorders. Currently, the main rule of HBO in AVN is an adjunctive therapy to control symptoms and improve the quality of life of a patient; however, the concept of using HBO as a primary treatment choice for AVN in patients with sickle cell disease is not well evaluated yet. In this case study, we reported a 15-year-old boy with sickle cell disease who was suffering from stage II AVN in bilateral femoral and right shoulder joints. A total of 57 sessions of HBO resulted in the complete resolution of AVN in post-treatment MRI.